Metallogenic Evolution of the Mackenzie and Eastern Selwyn Mountains of Canada’s Northern Cordillera, Northwest Territories:: A Compilation and Review - Ootes, Luke; Gleeson, Sarah; Turner, Elizabeth; Rasmussen, Kirsten; Gordey, Steve; Falck, Hendrick; Martel, Edith; Pierce, Kelly (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2013)
SUMMARY The Mackenzie and eastern Selwyn Mountains, Northwest Territories, Canada, are the northeast expression of the Cordilleran orogen and have a geologic history that spans the last one billion years. The region has undergone a diverse tectonic evolution, which is reflected in an equally diverse collection of mineral deposits and prospects. More than 300 of these deposits and prospects have been documented in this area of the Northwest Territories and here they are categorized into mineral deposit types and their mode of formation evaluated and highlighted. Stratiform/stratabound Cu–Ag occurrences are hosted in the Neoproterozoic Coates Lake Group, generally preserved in the hanging wall of the Cretaceous Plateau fault, and define a belt through the central part of the Mackenzie Mountains. Low-grade phosphatic stratiform iron (47.5% Fe) occurs as iron formation in the Neoproterozoic Rapitan Group in the very northwest of the Mackenzie Mountains. Sedimentary exhalative Zn–Pb (± Ba) deposits are preserved in Cambrian through Devonian strata of the Selwyn Basin in the eastern Selwyn Mountains. Numerous carbonate-hosted Zn–Pb (± base-metals) occurrences are located in the Paleozoic strata of the Mackenzie Platform in the Mackenzie Mountains. Cretaceous felsic-intermediate plutons, which occur throughout the eastern Selwyn Mountains, are associated with tungsten skarn (proximal to intrusions), base-metal skarn (distal from intrusions), rare metals, semi-precious tourmaline related to pegmatites, and vein-hosted emeralds. Other resources of potential interest include coal deposits, placer gold, and possible Carlin-type gold deposits that have recently been identified farther west in the Yukon.